Markups, import competition and exporting. (14th February 2020) - Caselli, Mauro; Schiavo, Stefano
Abstract: This paper analyses the relationship between markups and international trade at the firm level using a large sample of French manufacturing firms for the period 1995–2007. In particular, the paper investigates the effect of increasing import competition from China on firms' price–cost margins and the way in which exporting interacts with this effect. The results show robust evidence that firms in more direct competition with Chinese imports decrease their markups. However, firms that become exporters experience a smaller reduction in their price–cost margins. Consistent with these findings, the results also show that firms facing tougher competition from China are more likely to start exporting to avoid such competitive pressures.